Odpowiedzi

2009-11-04T17:19:50+01:00
A)6x+6y=10y
y=0.5+x
6x= 10(o,5+x)-6(0,5+x)
y=0,5+x
6x=5+10x-3+-6x
y=0,5+x
6x-10x+6x=2
y= 0,5 +x
2x= 2/:2
y=0,5+x
x=1
y=1,5

2009-11-04T17:27:56+01:00
A)6x+6y=10y
y=0.5+x
6x= 10(o,5+x)-6(0,5+x)
y=0,5+x
6x=5+10x-3+-6x
y=0,5+x
6x-10x+6x=2
y= 0,5 +x
2x= 2/:2
y=0,5+x
x=1
y=1,5
  • Użytkownik Zadane
2009-11-04T17:33:08+01:00
A)6(x+y)=10y
y-x=0,5
y=05+x

6(x+0.5+x)=10×(0.5+x)
6x+3+6x=10×(0.5+x)
12x+3=5+10x
2x=2
x=1
y=1+0.5
y=1.5

b)y-8x=0,8y
4x+5y=5,1
4x=5.1-5y /;4
x=5.1-5y/4
y-8(5.1-5y/4)=0.8y
y-(10.2-10y)=0.8y
y-10.2+10y=0.8y
10.4y=10.2 /:10.4
y=0.98
x=5.1-5×0.98/4
x=5.1-4.9/4
x=0.2/4=0.05

c)2y+5x=6y
3y+4x=7,75
y=7.75-4x/3

2(7.75-4x/3)+5x=6(7.75-4x/3)
(15.5-8x/3)+5x=46.5-24x/3 /×3
15.5-8x+15x=46.5-24x
15.5+3x=46.5-24x
24x+3x=46.5-15.5
27x=31 /:27
x=31/27


d)1,5y-6x=4,5y
4y+9x+11 i 2/3
e)10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10